Bladder exstrophy - epispadias complex in a newborn: a case report and review of literature - Paul N. Tolefac; Eugene Yeikec; Calypse Ngwasiri; Gregory Ekane Halle; Alain Mefire Chichom (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2018)
Background: Bladder exstrophy-epispadias complex (BEEC) is a rare congenital malformation of the genitourinary system usually associated with other malformations. Case summary: We report the case of a new born delivered vaginally at 39 weeks and 2 days of gestation with BEEC. Three prenatal ultrasound scans missed the diagnosis. Medical management was provided and the patient was discharged against medical advice 48 hours later upon refusing surgical intervention. Conclusion: The diagnosis and management of BEEC is a challenge in sub-Sahara Africa. Radiologists doing prenatal ultrasounds should check routinely to exclude foetal anomalies.